Real GDP: The Flawed Metric at the Heart of Macroeconomics - Blair Fix; Jonathan Nitzan; Shimshon Bichler (Real-World Economics Review, 2019)
The study of economic growth is central to macroeconomics. More than anything else, macroeconomists are concerned with finding policies that encourage growth. And by `growth', they mean the growth of real GDP. This measure has become so central to macroeconomics that few economists question its validity. Our intention here is to do just that. We argue that real GDP is a deeply flawed metric. It is presented as an objective measure of economic scale. But when we look under the surface, we find crippling subjectivity. Moreover, few economists seem to realize that real GDP is based on a non-existent quantum – utility. In light of these problems, it seems to us that much of macroeconomics needs to be rethought.
Keywords: E13; M41; P16; E01; C43; O4; 330; aggregation; national accounting; economic growth; neoclassical economics; quality change; utility